Tamm Review: Are fuel treatments effective at achieving ecological and social objectives? A systematic review - Kalies, Elizabeth L.; Yocom Kent, Larissa L. (Forest ecology and management, 2016)
[Display omitted] •Thinning and burning fuel treatments reduce fire severity compared to untreated areas.•Treatments reduce wildfire carbon emissions but may not increase total carbon storage.•Treatment effects on understory plants are highly variable.•Large data gaps remain in treatment effects on many ecological variables.•Anecdotal evidence suggests treatments can improve outcomes for lives and property. The prevailing paradigm in the western U.S. is that the increase in stand-replacing wildfires in historically frequent-fire dry forests is due to unnatural fuel loads that have resulted from management activities including fire suppression, logging, and grazing, combined with more severe drought conditions and increasing temperatures. To counteract unnaturally high fuel loads, fuel reduction treatments which are designed to reduce fire hazard and improve overall ecosystem functioning have been increasing over the last decade. However, until recently much of what we knew about treatment effectiveness was based on modeling and predictive studies. Now, there are many examples of wildfires burning through both treated and untreated areas, and the effectiveness of treatments versus no action can be evaluated empirically. We carried out a systematic review to address the question: Are fuel treatments effective at achieving ecological and social (saving human lives and property) objectives? We found 56 studies addressing fuel treatment effectiveness in 8 states in the western US. There was general agreement that thin+burn treatments had positive effects in terms of reducing fire severity, tree mortality, and crown scorch. In contrast, burning or thinning alone had either less of an effect or none at all, compared to untreated sites. Most studies focused on carbon storage agreed that treatments do not necessarily store more carbon after wildfire, but result in less post-wildfire emissions and less carbon loss in a wildfire due to tree mortality. Understory responses are mixed across all treatments, and the response of other ecological attributes (e.g., soil, wildlife, water, insects) to treatment post-wildfire represents an important data gap; we provide a detailed agenda for future research. Overall, evidence is strong that thin+burn treatments meet the goal of reducing fire severity, and more research is needed to augment the few studies that indicate treatments protect human lives and property.